Surgically assisted caudal anesthesia in a case of Ankylosing Spondylitis-An innovative approach - Paria Radhashyam; Chattopadhyay Ipsita (Wolters Kluwer Medknow Publications, 2019)
Anticipated difficult endotracheal intubation and impossibility of conventional methods of neuraxial blocks in Ankylosing Spondylitis (AS) led to our search for an alternative technique of regional anesthesia for total hip replacement surgery in such a patient. The approach undertaken was, after infiltration of the area with a local anesthetic drug, an orthopedic surgeon drilled the posterior wall of sacral hiatus and surgically created a small opening on it. A nerve stimulator needle was then introduced through this opening to get muscle twitches of the great toe, which helped in identification of the sacral epidural space. 30 ml of 0.5% injection ropivacaine was then deposited in this extradural space. Motor and sensory blocks developed within 10 minutes. The novel approach of surgically assisted drilling of the posterior wall of sacral hiatus may be established as an alternative approach to the classical caudal anesthesia when other alternatives fail.